Differentiated and anaplastic thyroid carcinoma: Major changes in the American Joint Committee on Cancer eighth edition cancer staging manual. (1st November 2017) - Perrier, Nancy D.; Brierley, James D.; Tuttle, R. Michael
ABSTRACT: Answer questions and earn CME/CNE This is a review of the major changes in the American Joint Committee on Cancer staging manual, eighth edition, for differentiated and anaplastic thyroid carcinoma. All patients younger than 55 years have stage I disease unless they have distant metastases, in which case, their disease is stage II. In patients aged 55 years or older, the presence of distant metastases confers stage IVB, while cases without distant metastases are further categorized based on the presence/absence of gross extrathyroidal extension, tumor size, and lymph node status. Patients aged 55 years or older whose tumor measures 4 cm or smaller (T1‐T2) and is confined to the thyroid (N0, NX) have stage I disease, and those whose tumor measures greater than 4 cm and is confined to the thyroid (T3a) have stage II disease regardless of lymph node status. Patients aged 55 years or older whose tumor is confined to the thyroid and measures 4 cm or smaller (T1‐T2) with any lymph node metastases present (N1a or N1b) have stage II disease. In patients who demonstrate gross extrathyroidal extension, the disease is considered stage II if only the strap muscles are grossly invaded (T3b); stage III if there is gross invasion of the subcutaneous tissue, larynx, trachea, esophagus, or recurrent laryngeal nerve (T4a); or stage IVA if there is gross invasion of the prevertebral fascia or tumor encasing the carotid artery or internal jugular vein (T4b). The same T definitions will be used for both differentiated and anaplastic thyroid cancer, but the basic premise of the anatomic stage groups will remain the same.CA Cancer J Clin 2018;68:55‐63. ©2017 American Cancer Society.